Confounding Effect of Large Vessels on MR Perfusion Images Analyzed with Independent Component Analysis - Carroll, Timothy J.; Haughton, Victor M.; Rowley, Howard A.; Cordes, Dietmar (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: First pass contrast-enhanced MR imaging using gradient-echo acquisitions is commonly used to assess cerebral blood flow, despite the confounding signal from large blood vessels. We hypothesized that removal of this unwanted intravascular signal using independent component analysis would result in a more accurate depiction of cerebral blood flow.METHODS: Images of 11 patients, acquired with our acute stroke imaging protocol, were post processed to produce images of relative cerebral blood flow (rCBF). The same images were processed with independent component analysis to identify and remove the signal from large blood vessels, with a second set of rCBF images produced. Both sets of rCBF maps were pooled, randomized in order, and read in a blinded fashion by two neuroradiologists to assess the level of large artery artifact and overall image quality. Significance was determined using a Wilcoxon signed rank test.RESULTS: Results from both readers indicated that the level of large artery artifact was significantly reduced in the images processed using independent component analysis component removal (P < .05). In addition, both readers indicated significantly (P < .05) improved image quality of the images processed using independent component analysis.CONCLUSION: The removal of the signal resulting from large blood vessels before calculation of rCBF resulted in images with significantly less artifact and higher image quality.